Forecasting and product allocation process of LG - Butterfly Marketing Limited - Afrad, Md. Mahboob Jahan (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.